PENERAPAN ALAT PENDETEKSI KESUBURAN TANAH DAERAH PERTANIAN DI DAERAH TANAH GARAM KOTA SOLOK - Oknovia Susanti; Gihan Elja; M. Alfa Rizki (Jurnal Hilirisasi IPTEKS, 2022)
Soil fertility is a basic component to produce quality agricultural products so that farmers enjoy the results they have fought for continuously. Therefore, a tool was created to help the community in the process of agricultural processing, one of which is by producing a tool to detect soil fertility while farmers are cultivating it. The tool is made in a very simple way using a 100 watt light bulb, 1 inch pipe, T pipe, 2 plugs, 2 electrical wires containing one (red 1 meter black 2 meters), light fittings, glue, plaster/duct tape. Soil fertility check tool made as much as 2 pieces. The working principle of this tool uses the principle of ohm's law (Ω), where when a medium has a small resistance value, the electric voltage it transmits. If there are many of these cations in the soil, the soil can be said to be fertile. But on the contrary, if the light is dim or does not light up, then the conducting value in the soil is of little value, and the soil can be said to be infertile. The demonstration of this soil fertility checker was carried out directly to farmer groups in the hill rice fields, Solok city. The demonstration of making this tool is expected to provide information to farmer groups on how to make simple tools and check their soil without having to buy expensive soil pH measuring devices. The main points conveyed: the meaning of soil fertility and a demonstration of how to make a simple soil fertility check tool.